2019
DOI: 10.1002/adbi.201900064
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐Targeted Cyclic Forces Accelerate Neural Tube‐Like Rosette Formation from Human Embryonic Stem Cells

Abstract: and cell replacement therapy. For example, recent demonstration that hESCs can be induced to differentiate and become motor neurons (MNs) offers unprecedented opportunity for studying MN development/function and developing cell-based therapies. [2] However, current MN differentiation protocols, based on soluble factors and small molecules that inhibit and/ or stimulate particular signaling pathways in defined culture conditions, not only are limited by low differentiation purity and yield, but also require pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Modulation of YAP activity is necessary for hPSCs to exit pluripotency and begin differentiation into specific lineages 21 , 29 , 44 , 45 . Our observation of decreased OCT4 in hPSCs after ATC application is consistent with our previous results 28 , 30 , indicating that the hPSCs were undergoing differentiation due to ATC application. However, YAP nucleocytoplasmic translocation in hPSCs after 30 min ATC treatment was observed in our previous study 28 rather than nuclear translocation observed in our current study.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Modulation of YAP activity is necessary for hPSCs to exit pluripotency and begin differentiation into specific lineages 21 , 29 , 44 , 45 . Our observation of decreased OCT4 in hPSCs after ATC application is consistent with our previous results 28 , 30 , indicating that the hPSCs were undergoing differentiation due to ATC application. However, YAP nucleocytoplasmic translocation in hPSCs after 30 min ATC treatment was observed in our previous study 28 rather than nuclear translocation observed in our current study.…”
Section: Resultssupporting
confidence: 93%
“…Our data of rapid downregulation of OCT4 in hPSCs by ATC (as short as 1 min) show the early mechanoresponses of hPSCs, showing their unique mechanosensitivity to ATC stimulations and the likely role in the long-term effects on hPSCs after ATC treatments manifested as faster differentiation and neural rosette formation 28 , 30 .…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations